Training and match-related head acceleration events in top level domestic senior women's and men's Rugby Union: A multi-league instrumented mouthguard study - Roe, G.; Sawczuk, T.; Tooby, J.; Hudson, S.; White, R.; Mackay, L.; Owen, C.; Starling, L.; Cross, M.; Falvey, É.; Hendricks, S.; Kemp, S.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2024)
The aim of this study was to investigate the difference in head acceleration event (HAE) incidence between training and match-play in women's and men's players competing at the highest level of domestic rugby union globally. Players from Women's (Premiership Women's Rugby, Farah Palmer Cup) and Men's (Premiership Rugby, Currie Cup) rugby union competitions wore instrumented mouthguards during matches and training sessions during the 2022/2023 seasons. Peak linear (PLA) and angular (PAA) acceleration were calculated from each HAE and included within generalized linear mixed-effects models. The incidence of HAEs was significantly greater in match-play compared to training for all magnitude thresholds in both forwards and backs, despite players spending approximately 1.75-2.5 times more time in training. For all HAEs (PLA > 5 g and PAA > 400 rad/s2), incidence rate ratios (IRRs) for match versus training ranged from 2.80 (95% CI: 2.38-3.30; men's forwards) to 4.00 (3.31-4.84; women's forwards). At higher magnitude thresholds (PLA > 25 g; PAA > 2000 rad/s2), IRRs ranged from 3.64 (2.02-6.55; PAA > 2000 rad/s2 in men's backs) to 11.70 (6.50-21.08; PAA > 2000 rad/s2 in women's forwards). Similar trends were observed in each competition. Players experienced significantly more HAEs during match-play than training, particularly at higher magnitude thresholds. Where feasible, HAE mitigation strategies may have more scope for HAE reduction if targeted at match-play, particularly where higher magnitude HAEs are the primary concern. However, the number of HAEs associated with different training drills requires exploration to understand if HAEs can be reduced in training, alongside optimizing match performance (e.g., enhancing contact technique).